High-fat diet and fructose drink stimulate apoptotic signaling via cleaved caspase-3 protein in hepatic cells of rats - Freire, Lorena Silva; Silva, Franciely Alves da; Lima, Thiago da Rosa; Ávila, Eudes Thiago Pereira; Damazo, Amilcar Sabino; Pereira, Mayara Peron; Santos, Stephanie Figueiredo; Lemes, Suelem Aparecida de França; Gai, Bibiana Mozzaquatro; Kawashita, Nair Honda (ABCS Health Sciences, 2025)
Introduction: The intake of a high-fat, high-fructose diet during childhood may lead to obesity, hepatic steatosis, and inflammation in adulthood. Objective: To investigate the effects on hepatic metabolism of intake of diets with various levels of fat associated with fructose drinks during childhood. Methods: Male 21-days-old rats were divided into groups: Control (C, 16.3% kcal from lipids diet and water); High-fat (HF, 45% kcal from lipids diet and fructose drink); and very high-fat (VHF, 60% kcal from lipids diet and fructose drink). After 10 weeks, blood and liver were collected for biochemical, histological, lipid profile, and Western blotting analyses. Results: The HF and VHF animals presented higher adiposity index, hepatic accumulation of lipids, and inflammatory cells, suggesting the treatments were effective at inducing non-alcoholic fatty liver disease in its inflammatory form. The hepatic content of cleaved caspase-3 and deposition of collagen fibers were increased in the HF group. Conclusion: In summary, lipid-rich diets combined with fructose drinks seem to promote the increase in body lipids content and accumulation of lipids, inflammation, activation of apoptotic signaling pathways, and the initiation of a fibrotic process in the liver in adulthood.